Physiological monitoring of the Olympic athlete - Davison, R. R.; van Someren, K. A.; Jones, A. M. (Journal of Sports Sciences, 2009)
As the winning margin in Olympic competition is so small, there is a continuous quest for improvements in the preparation of athletes at this standard. Therefore, even the smallest physiological improvements that result from modifications in training strategy, preparation regime or ergogenic aids are potentially useful. Unfortunately, there is a lack of research data on elite competitors, which limits our interpretation of current literature to the elite sporting environment. This places extra responsibility on the physiologist to carefully consider the most appropriate physiological variables to monitor, the best protocols to assess those variables, and the accurate interpretation of the test results. In this paper, we address the key issues of ecological validity, measurement error, and interpretation for the most commonly monitored physiological variables. Where appropriate, we also indicate areas that would benefit from further research.